On Initial Conditions for the Lattice Boltzmann Method (Communications in Computational Physics, 2018)
In this paper, we propose two initialization techniques for the lattice Boltzmannmethod. The first one is based on the theory of asymptotic analysis developed in[M. Junk and W.-A. Yong, Asymptotic Anal., 35(2003)]. By selecting consistent macroscopicquantities, this initialization leads to the second-order convergence for bothvelocity and pressure. Another one is an improvement of the consistent initial conditionsproposed in [R. W. Mei, L.-S. Luo, P. Lallemand and D. d'Humières, Comput.Fluids, 35(2006)]. The improvement involves a modification of the collision term anda reconstruction step. Numerical examples confirm the accuracy and efficiency of ourtechniques.